PENGUATAN NILAI-NILAI KEARIFAN LOKAL PADA PEMBELAJARAN MUATAN LOKAL AKSARA INCUNG - Nandia Pitri; Ogi Sandria (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Incung script is an ancient script native to the Kerinci community that contains a long historical meaning. This script is the local wisdom of the Kerinci people which contains tembo and karang mindu as well as mantras. This script is also used to write literature, and customary laws written on bark, buffalo horns, bamboo and palm leaves. The values contained in the Incung script serve as a basis for character building. The values contained can also be a reinforcement of attitudes in learning at school, contributing to building better student character. Therefore, character building is very important to be carried out through learning, especially through strengthening character values sourced from local wisdom carried out in the process of learning history at school. This is very relevant because history learning has an important role in the character building process that seeks to educate students to have more reflective thinking and meaningful learning. The method used in this research is descriptive-qualitative with a literature study approach and methodological review between local content learning related to character building strategies and value education. This article consists of three steps, as follows: 1) Conducting a literature study and methodological review, 2) Analyzing the literature data and proposing new ideas, 3) reporting the results of the analysis. This article describes an innovative form of local content learning that is integrated with strengthening the local wisdom values of the Sungai Penuh community so that it can contribute to student character building. The strengthened local wisdom values integrated are religion, responsibility, courage, independence, honor, care, intellectual, tolerance, movement, and solidarity. In summary, this paper formulates another strategy in value education through local content learning that is relevant to the goal of building better student character.